Short term atmospheric pressure cold plasma treatment: A novel strategy for enhancing the substrate utilization in a thermophile, Geobacillus sp. strain WSUCF1. (April 2019) - Rathinam, Navanietha K.; Gorky; Bibra, Mohit; Rajan, Magesh; Salem, David; Sani, Rajesh K.
Highlights: Resistance of thermophilic Geobacillus sp. WSUCF1 to cold plasma treatment. Role of cold plasma in improving substrate utilization is reported. Cold plasma treatment in WSUCF1 enhances the biofilm formation. Cold plasma treatment improves the biomass yield. Abstract: The aim of this study was to investigate the effect of atmospheric pressure cold plasma on the microbial substrate utilization and biomass yield in a thermophilic strain. Geobacillus sp. strain WSUCF1, a thermophile capable of producing cellulolytic enzymes with higher activity was used for this investigation. Treatment with cold plasma for 4 min increased the rates of glucose utilization by 74% and biomass yield by 60% when compared with the control. WSUCF1 treated with plasma also displayed enhanced biofilm formation. This study for the first time, reports the use of cold plasma for enhancing the substrate utilization and biofilm formation in a thermophile.